#SouPavulagem': A relação entre o Arraial da Pavulagem (Belém-PA), tradição e representação social na internet - Santos, Gianne Regina Conceição dos (2017)
This paper analyzes Arraial do Pavulagem, an education and popular culture instituition localized in the city of Belém do Pará, and how it appropriates modern tools, such as Internet and social networks, to spread the traditional knowledge and the culture of Pará. Participant observation and documentary research were the methodologies used to understand the founders of the institution, complemented with open interviews.